High‐level of resistance to spinosad, emamectin benzoate and carbosulfan in populations of Thrips tabaci collected in Israel. Issue 2 (24th August 2012) - Lebedev, Galina; Abo‐Moch, Fauzi; Gafni, Guy; Ben‐Yakir, David; Ghanim, Murad
Abstract BACKGROUND: The onion thrips, Thrips tabaci Lindeman, is a major pest of several crop plants in the genus Allium, such as onions, garlic and chives. In Israel, these crops are grown in open fields and in protected housing. This thrips is usually controlled by the application of chemical insecticides. In recent years, spinosad, emamectin benzoate and carbosulfan have been the major insecticides used for the control of the onion thrips. In the last 4 years, growers of chives and green onion from several regions of Israel have reported a significant decrease in the efficacy of insecticides used to control the onion thrips. RESULTS: The susceptibility of 14 populations of the onion thrips, collected mainly from chives between the years 2007 and 2011, to spinosad, emamectin benzoate and carbosulfan was tested using a laboratory bioassay. The majority of the populations showed significant levels of resistance to at least one of the insecticides. LC50 values calculated for two of the studied populations showed that the resistance factor for spinosad compared with the susceptible population is 21 393, for carbosulfan 54 and for emamectin benzoate 36. Only two populations, collected from organic farms, were susceptible to the insecticides tested. CONCLUSION: This is the first report of a high resistance level to spinosad, the major insecticide used to control the onion thrips. Resistance cases to spinosad were associated with failures to control the pest. Populations resistant to spinosad also had partial or complete resistance to other insecticides used for controlling the onion thrips. Copyright © 2012 Society of Chemical Industry